ANXIETY MANAGEMENT METHODS THROUGH PHYSICAL ACTIVITY IN PREGNANT WOMEN: A LITERATURE REVIEW - Nur Ilmya Nugraha Ningrum Irfandi Putri; Riska Oktaviana; Rery Afianto; Puspitasari, Nunik (UNIVERSITAS AIRLANGGA, 2025)
Background: Anxiety and depression are the most common mental disorders in the peripartum period. Therefore, this study will examine more deeply the treatment of anxiety through physical activity in pregnant women. In Indonesia, there are 373,000,000 cases of anxiety that occur in pregnant women. A total of 107,000,000 or around 28.7% of these cases occur in pregnant women before the delivery process (RI, 2018). Therefore, this study will examine more deeply the management of anxiety through physical activity in pregnant women. Method: This study uses the Narrative Literature Review method, which begins with reading various relevant articles carefully, then summarizing, drawing conclusions, and identifying gaps that are relevant to the topic or research question. The article search used the following keywords: method AND managing OR reducing AND anxiety AND physical activity OR exercise OR yoga OR aerobic AND pregnant women. The inclusion criteria used in this research article are articles that discuss methods of managing anxiety through physical activity (all types of physical activity) in pregnant women. The articles used must be published in the range of 2020 to 2024 and fully accessible, and in Indonesian or English. The synthesis results found a total of 10 articles that met the inclusion criteria. Result: The review found that physical activity has positive benefits in reducing anxiety levels in pregnant women. Physical activity can be an effective strategy in managing anxiety through the influence of hormones and various psychosocial mechanisms. Various types of physical activity, such as moderate exercise, strength training, and yoga, can improve mood and reduce symptoms of depression and anxiety through biochemical and physiological processes. Therefore, the recommendation given by practitioners to pregnant women is to engage in moderate-intensity aerobic physical activity for at least 150 minutes per week.